Impact of Mining Activities Against Sand Stone Sustainability Agricultural Resources and Power Lenek In the village of Desa Lenek Kali Bambang District of Aikmel - In, Nurul -; Sriartha, I Putu; Citra, Putu Ananda (Media Komunikasi Geografi, 2016)
This research was conducted in the village of Lenek Daya and Kali Bambang, District of Aikmel, East Lombok. This study aims to: (1) to describe the characteristics of sand mining activities rocks in the village of Lenek Daya and Kali Bambang District of Aikmel, (2) Describe the process of the development of the management of sand mining activities rocks in the village of Lenek Daya and Kali Bambang District of Aikmel, ( 3) to analyze the impact of sand mining activities stones on the sustainability of agricultural resources in the village Lenek Daya and Kali Bambang District of Aikmel. This research is a analysis descriptive quantitative and qualitative. These samples included 71 people taken by "Proportional Random Sampling". The object of this research is the mining and agricultural activities while research, subjects were the miners sandstone, the rock sand mining, and agricultural land owners who used stone sand mining area in the Village Lenek Daya and Kali Bambang. Data obtained using the survey method with the instrument in the form of a questionnaire. The results showed that (1) Characteristics of sand mining activities rocks in the village of Lenek Daya and Kali Bambang District of Aikmel is in terms of age 77% of miners are productive age, education miners 42% completed primary school, the miners 98% indigenous population, 79% miners income of at least Rp 50,000/day, and 42.1% of sales sandstone sold to local village construction purposes, (2) sandstone mining activities which took place in the village and the Lenek Daya and Kali Bambang District of Aikmel managed by rural communities dan last times proposed by rural communities, 72% use manual equipment and 28% modern equipment,(3) rock sand mining activities negatively affect the sustainability of agricultural resources with a level of sustainability categorized â€lowâ€.Â Keywords: Characteristics of stone sand mining activities, and agricultural resources.